BIOCHEMICAL AND PHYSIOLOGICAL CHANGES IN RESPONSE TO SALINITY IN LEAVES AND ROOTS OF TWO DURUM WHEAT (TRITICUM DURUM DESF.) GENOTYPES - Bouthour, Donia; Kalai, Tawba; Gouia, Houda; Chiraz, Chaffei-Haouari (Plant Breeding and Seed Science, 2016)
Salt stress is a major abiotic stress that limits agricultural productivity in many regions of the world. To understand the molecular basis of the salt stress response, two wheat (Triticum durum Desf.) cultivars, Karim and Azizi, which are of agronomic significance in Tunisia, were grown under non-saline and saline conditions (100 mM). Leaves and roots of control and salt-stressed plants were harvested after 11 days of salt treatment. Karim cultivar may behave as a typical Na+ include, which compartmentalizes Na+ within the leaf cell vacuoles where it could be used as an osmoticum to lower the osmotic potential necessary for the maintenance of the plant hydric status. While, accumulation of K+ was greater in Karim cultivar compared to Azizi, in both organs, presenting an important manifestation of salinity tolerance. Significant changes in metabolism of antioxidative system were observed, with an increase in protein tyrosine nitration, which indicates that salinity stress induces a nitro-oxidative stress.